PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI INDONESIAKU KAYA BUDAYA KELAS IV SD NEGERI 060923 MEDAN AMPLAS - Zihan Rahmayani; Nurmairina; Ahmad Landong; Umar Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of the research was to improve student learning outcomes in Natural and Social Sciences (IPAS) through the application of the Problem-Based Learning (PBL) model. The subjects were fourth-grade students of SD Negeri 060923 Medan Amplas. The method used was Classroom Action Research (CAR), implemented in two cycles, each consisting of three meetings. Each cycle consisted of planning, implementation, observation, and reflection. Data collection techniques included learning outcome tests, observation of student activities, and documentation. The results showed that the application of the Problem-Based Learning (PBL) model can improve students’ learning outcomes. This is evident in the increase in the average student learning achievement score from 45% in the pre-cycle to 65% in the cycle I and then to 89% in the II cycle. Thus, the implementation of Problem-Based Learning has proven effective in improving the science learning outcomes of fourth-grade students at SD Negeri 060923 Medan Amplas.